Sports Performance and Intermittent Fasting: Impact on Training and Results, Mechanisms and Health Benefits in Weight Management, Metabolic Health, and Chronic Diseases – A Review of Risks, Current Evidence, and Future Research Directions - Bieńko, Mateusz; Rutkowska, Marta; Król, Tomasz; Toborek, Michalina; Marchaj, Magdalena; Korta, Karolina; Putra, Anna; Niedziela, Natalia; Margas, Mikołaj (Quality in Sport, 2024)
Introduction: Intermittent Fasting (IF) has become a popular method in the contemporary medical world as an up-to date technique of the health and wellbeing in the last several years. Purpose: This research aims to investigate the both impact of IF on sports performance and therapeutic potential of IF on cardiovascular, metabolic and neurological diseases with focus on obesity, diabetes and impact on cardiometabolic risk. State of Knowledge: Intermittent fasting has been found to extend both life and health span by positively impacting weight management, reducing the risk of cardiovascular incidents, promoting cellular repair, and exhibiting anti-inflammatory actions. It improves blood sugar levels, provides protection against hepatosteatosis, enhances lipid metabolism and has beneficial effects on the brain-gut-microbiome system. IF leads to improved mental performance and offers benefits for neurological disorders such as epilepsy, Alzheimer’s, and multiple sclerosis IF has shown beneficial effects on body composition and lean muscle mass without compromising physical performance nor impair strength. However, concerns about nutritional deficiencies, sustainability, and social implications are evident. Common drawbacks of IF include feelings of hunger, irritability, fatigue and hypoglycemia risk. IF is not recommended for pregnant woman and individuals suffering from eating disorders. Conclusions: IF is as a promising tool alongside traditional therapeutic strategies, particularly for addressing obesity, diabetes, and managing cardiovascular risk. For athletes it is a valuable tool in managing fat-mass particularly combined with high-intensity interval training (HIIT). However it is not recommended for certain groups. The diverse landscape of IF patterns, coupled with drawbacks, underscores the necessity for long-term research before routinely recommending IF for athletes and patients.